Acto-myosin force organization modulates centriole separation and PLK4 recruitment to ensure centriole fidelity - Elisa Vitiello (Nature Portfolio, 2019)
Centriolar separation is thought to be crucial for centriole duplication, but the mechanism behind separation is poorly understood. Here, using micropatterning, the authors report that actomyosin forces influence the direction, distance, and time of centriole separation.